HUBUNGAN MOTOR EDUCIBILITY, KETERAMPILAN BOLA VOLI DAN KEBUGARAN JASMANI TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMA IT KAIMAS: HUBUNGAN MOTOR EDUCIBILITY, KETERAMPILAN BOLA VOLI DAN KEBUGARAN JASMANI TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMA IT KAIMAS - Naufal Elang Krisma; Asep Angga Permadi; Z. Arifin (Jurnal Porkes, 2026)
This study aims to analyze the relationship between motor educability, volleyball skills, and physical fitness on physical education learning outcomes at SMA IT Kaimas. This study employs a quantitative approach using a comparative causal method. The study sample consisted of 16 tenth-grade students selected using total sampling. The research instruments included a motor educability test (IOWA Brace Test), a volleyball skills test (underhand pass, overhand pass, underhand serve, overhand serve, and smash), and a physical fitness test (bleep test). Data analysis techniques used prerequisite tests (normality and homogeneity tests) as well as Pearson’s correlation test to test the hypotheses. The results of the normality and homogeneity tests showed that all data were normally distributed and homogeneous (p > 0.05). The correlation test results showed that physical fitness (r = 0.315), volleyball skills (r = 0.304), and motor educability (r = 0.394) had a positive relationship with Physical Education learning outcomes, but were not statistically significant (p > 0.05). Motor educability showed the highest correlation coefficient compared to the other variables. These findings indicate that although not yet significant, improvements in physical fitness, sports technical skills, and motor learning ability still play a strategic role in supporting PJOK learning outcomes.